PRICING IN THE TRANSACTION OF BUYING AND SELLING CLOTHES WITH MURABAHAH CONTRACT BY MSMES IN GAMPONG RUMPET, ACEH BESAR - M. Deri Andrian (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study aims to analyze pricing practices in clothing sales transactions conducted by Micro, Small, and Medium Enterprises in Gampong Rumpet from the perspective of the murabahah contract in Islamic jurisprudence (fiqh muamalah). The main focus of this research lies in the pricing mechanism applied by MSME actors and its conformity with the principles of transparency regarding cost price and clarity of profit margin, which constitute the essential characteristics of the murabahah contract. This research employs an empirical legal method using a case approach and a conceptual approach. Data were collected through interviews, observations, and literature review, and subsequently analyzed using qualitative descriptive analysis. The findings indicate that pricing practices among MSMEs in Gampong Rumpet generally involve disclosing only the final selling price without informing consumers of the cost price and profit margin, thereby failing to fully comply with the requirements of a murabahah contract. This condition has the potential to give rise to elements of gharar (uncertainty) and an imbalance in bargaining positions, which contradicts the principles of justice and equality in Islamic economics. Therefore, this study recommends the need for education and assistance for MSME actors regarding the application of a simplified murabahah model that nonetheless upholds the principles of transparency and fairness in order to realize transactions in accordance with Islamic values.